Volume 4: Turbo Expo 2004 2004
DOI: 10.1115/gt2004-53394
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Gas Ingestion Through Axial-Flow Turbine Rim Seals

Abstract: It has been suggested by researchers that ingestion, through rim seals, of mainstream gas into axial-flow turbine disk cavities is a consequence of the prevailing unsteady three-dimensional flow field. The cause-effect relationship is complex — to help understand it, experiments were performed in a model single-stage turbine rig using two different vane-blade configurations. Selected measurements from one of the configurations were reported earlier (1999–2001). The second configuration is new, featuring smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Experiments by Cao et al., 11 Jakoby et al., 24 Schädler et al., 34 Roy et al., 35 Savov et al., 36 Town et al. 37 and Beard et al.…”
Section: Rotating Flow Modes and Cfd Modellingmentioning
confidence: 99%
“…Experiments by Cao et al., 11 Jakoby et al., 24 Schädler et al., 34 Roy et al., 35 Savov et al., 36 Town et al. 37 and Beard et al.…”
Section: Rotating Flow Modes and Cfd Modellingmentioning
confidence: 99%
“…Interaction between the blade and vane flows may also be important. Recent CFD and experimental studies [3,[11][12][13] have shown that at low sealing flow rates unsteady flow features, unrelated to the blade passing frequency, are important and that complete 360 deg models may be required to fully represent these features. Flow structures similar to those identified for ingestion due to disc pumping have been identified in CFD solutions, and confirmed experimentally by unsteady pressure measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the main gas path annulus was reduced to include span locations only from the hub to mid-span on the airfoils, resulting in half-span turbine vanes and blades. This approach has been successfully performed and reported in the literature by other researchers including Feiereisen [30] and Roy [13][14], and allowed the air flow capacity requirements to be cut approximately by half for Phase 1. Current plans for the long term Phase 2 operation include doubling the air mass flow rate capability to near 11.4 kg/s (25 lbm/s) by adding a second identical large compressor, in parallel with the first compressor, that will allow studies to be performed using full span airfoils, larger turbine disk diameters, higher rotational speeds (higher Re), and additional turbine stages.…”
Section: Facility Requirementsmentioning
confidence: 96%